2013
DOI: 10.1111/bph.12204
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged inhibition of 5‐HT3 receptors by palonosetron results from surface receptor inhibition rather than inducing receptor internalization

Abstract: Background and PurposeThe 5-HT3 receptor antagonist palonosetron is an important treatment for emesis and nausea during cancer therapy. Its clinical efficacy may result from its unique binding and clearance characteristics and receptor down-regulation mechanisms. We investigated the mechanisms by which palonosetron exerts its long-term inhibition of 5-HT3 receptors for a better understanding of its clinical efficacy.Experimental ApproachCell surface receptors (recombinantly expressed 5HT3A or 5HT3AB in COS-7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
(99 reference statements)
2
19
0
Order By: Relevance
“…[13][14][15][16] Recently observations of multiple modes of inhibition by palonosetron, for example, exhibiting pseudo irreversible inhibition at the serotonin site but also acting at a distinct allosteric site, exemplifies the complexity of modulation and challenges to medicinal chemists. [17][18][19][20][21] …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Recently observations of multiple modes of inhibition by palonosetron, for example, exhibiting pseudo irreversible inhibition at the serotonin site but also acting at a distinct allosteric site, exemplifies the complexity of modulation and challenges to medicinal chemists. [17][18][19][20][21] …”
Section: Introductionmentioning
confidence: 99%
“…Hothersall et al (19) reported that palonosetron acts as a 5-HT3 receptor over a prolonged period or even as an irreversible antagonist for at least 4 days. Allosteric receptor-receptor interactions may play a significant role in this phenomenon (19). The key objective of the present study was to identify a continuous daily regimen of anti-emetic drugs that may be used during remission induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, palonosetron treatment was shown to down-regulate the amount of available 5-HT 3 receptor binding sites, rather than cell surface expression levels of 5-HT 3 receptors [18]. This result suggests that palonosetron inhibits 5-HT 3 receptors by interacting with an allosteric binding site rather than by inducing receptor internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Palonosetron exhibits significant receptor occupation for as long as 4 days [18]. Given this characteristic of palonosetron, we investigated the effects of continuous infusion in the context of a PCA on the incidence of PONV in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%